Relationship Between Dietary Fiber and Vitamin C Intake and Oral Cancer - Wang, Jing; Fan, Yi; Qian, Jiawen; Wang, Sijie; Li, Yanni; Xu, Mingming; Chen, Fa; Wang, Jing; Qiu, Yu; Lin, Lisong; He, Baochang; Liu, Fengqiong (Frontiers in Public Health, 2022)
Background: Dietary fiber and vitamin C has been reported to play a possible role in tumorigenesis. However, few studies have estimated their association with oral cancer risk. In this project, we investigated the relationship between dietary fiber and vitamin C and oral cancer risk in adults in Southern China. Methods: 382 patients newly diagnosed with oral cancer were matched to 382 hospital derived controls by frequency matching in age and sex. Pre-diagnostic consumption of dietary fiber and vitamin C intake were measured through food frequency questionnaire. Association between nutrients intake and oral cancer risk were evaluated by logistic regression. OR value and 95% confidence interval was calculated. Results: Intake of dietary fiber and vitamin C was significantly lower in oral cancer patients （8.15 g/day)than in control participants（8.88 g/day). Increased dietary fiber or vitamin C intake was linked to a decreased incidence of OC after adjustment of age, marital status, residence, BMI, occupation, education，tobacco smoking, alcohol consumption and family history of cancer(Ptrend <0.001). Compared with the lowest tertile, the adjusted OR of the top tertile of dietary fiber was 0.47 (95 % CI 0.32, 0.68). While the adjusted OR of the highest tertile was 0.60 (95 % CI 0.42,0.87) compared with the lowest tertile of vitamin C. Conclusions: Dietary intake of fiber and vitamin C were lower in oral cancer patients than in control participants. Dietary fiber and vitamin C were inversely related to risk of oral cancer risk.